((y+8)*(y+8))-40=0

Simple and best practice solution for ((y+8)*(y+8))-40=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for ((y+8)*(y+8))-40=0 equation:


Simplifying
((y + 8)(y + 8)) + -40 = 0

Reorder the terms:
((8 + y)(y + 8)) + -40 = 0

Reorder the terms:
((8 + y)(8 + y)) + -40 = 0

Multiply (8 + y) * (8 + y)
((8(8 + y) + y(8 + y))) + -40 = 0
(((8 * 8 + y * 8) + y(8 + y))) + -40 = 0
(((64 + 8y) + y(8 + y))) + -40 = 0
((64 + 8y + (8 * y + y * y))) + -40 = 0
((64 + 8y + (8y + y2))) + -40 = 0

Combine like terms: 8y + 8y = 16y
((64 + 16y + y2)) + -40 = 0
(64 + 16y + y2) + -40 = 0

Remove parenthesis around (64 + 16y + y2)
64 + 16y + y2 + -40 = 0

Reorder the terms:
64 + -40 + 16y + y2 = 0

Combine like terms: 64 + -40 = 24
24 + 16y + y2 = 0

Solving
24 + 16y + y2 = 0

Solving for variable 'y'.

Begin completing the square.

Move the constant term to the right:

Add '-24' to each side of the equation.
24 + 16y + -24 + y2 = 0 + -24

Reorder the terms:
24 + -24 + 16y + y2 = 0 + -24

Combine like terms: 24 + -24 = 0
0 + 16y + y2 = 0 + -24
16y + y2 = 0 + -24

Combine like terms: 0 + -24 = -24
16y + y2 = -24

The y term is 16y.  Take half its coefficient (8).
Square it (64) and add it to both sides.

Add '64' to each side of the equation.
16y + 64 + y2 = -24 + 64

Reorder the terms:
64 + 16y + y2 = -24 + 64

Combine like terms: -24 + 64 = 40
64 + 16y + y2 = 40

Factor a perfect square on the left side:
(y + 8)(y + 8) = 40

Calculate the square root of the right side: 6.32455532

Break this problem into two subproblems by setting 
(y + 8) equal to 6.32455532 and -6.32455532.

Subproblem 1

y + 8 = 6.32455532 Simplifying y + 8 = 6.32455532 Reorder the terms: 8 + y = 6.32455532 Solving 8 + y = 6.32455532 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-8' to each side of the equation. 8 + -8 + y = 6.32455532 + -8 Combine like terms: 8 + -8 = 0 0 + y = 6.32455532 + -8 y = 6.32455532 + -8 Combine like terms: 6.32455532 + -8 = -1.67544468 y = -1.67544468 Simplifying y = -1.67544468

Subproblem 2

y + 8 = -6.32455532 Simplifying y + 8 = -6.32455532 Reorder the terms: 8 + y = -6.32455532 Solving 8 + y = -6.32455532 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-8' to each side of the equation. 8 + -8 + y = -6.32455532 + -8 Combine like terms: 8 + -8 = 0 0 + y = -6.32455532 + -8 y = -6.32455532 + -8 Combine like terms: -6.32455532 + -8 = -14.32455532 y = -14.32455532 Simplifying y = -14.32455532

Solution

The solution to the problem is based on the solutions from the subproblems. y = {-1.67544468, -14.32455532}

See similar equations:

| -1/5+-2=4 | | 4+3(h+1)=4h+6 | | 2.50=1201.10 | | 9-2k=11 | | -1/50+-2=4 | | 10[y+5]=10 | | 500=45x+35(12-x) | | 11-8x-4x^2=0 | | 9y=9y-15 | | 9x-2+5(x+9)=85 | | 77x+25x=400+25x | | -15x+11=86 | | 3x+6(x+5)=-51 | | 2x+200=800-22x | | 166=s+s+2+26+s | | 166=s+s+2+26s | | 10c-9=8c+5 | | 10-2(x+3)=4 | | -14+3n+30=14n+28+n | | 11m+2n+4m-n= | | (4/9)(5/18) | | 14a-4a+5a-3a= | | 5+18/2*4 | | -2+x/-2=-12 | | 3w+7=-5 | | 2(3r-4)-6(t+1)=-t+4(t+10) | | 3+22+5x=10x | | 4/9x5/18 | | -6=x/-13-2 | | 3y+4=4 | | X/2+5=25 | | 7(y+4)=2x+5 |

Equations solver categories